Glucose Tolerance Factor Activity of Binary Amino acid Chromium Complexes in Animals and Yeast - Karthikeyan, K.S.; Rajender, M.; Shilpa, M.; Sastry, K. Sivarama (International Journal of Bio-resource and Stress Management, 2023)
This study has evaluated the role of ammo acid - chromium complexation in Glucose Tolerance factor (GTF from yeast has long been known to have trivalent chromium presumably complexed to several amino acid residues but structural details have remained elusive. In this investigation, AA.Cr (AA=amino acid, AA:Cr3+ =1:1) synthesized with AA being glutamine, cysteine, glycine, - the putative ligands in GTF-, as also phenylalanine and lysine have been individually examined for their abilities to enhance rates of glucose metabolism in yeast as well as for their GTF activity in the Oral Glucose Tolerance test (OGTT) in rats. For the first time, seminal findings have been made which established that some AA.Cr exhibit powerful and intrinsic GTF activity in both experimental systems with Gln.Cr > Cys.Cr> Gly.Cr>Phe.Cr. This revealed that binary complexes themselves possess necessary and sufficient structure(s) that endow them with GTF activity. Since Phe.Cr was also active, the amino acids presumed to be important in GTF, are not necessarily the only ones with this property. Furthermore, Lys.Cr was found herein to be totally inactive as GTF suggesting that several, but not a with AA.Cr have been discussed, in the context of the role of chromium in cellular metabolism